Análisis de la región de control “D-Loop” del ADN mitocondrial de mestizos ecuatorianos mediante secuenciación Sanger - Yépez Santos, José Ignacio (2019)
The Ecuadorian population is composed of three well-defined ethnic groups: indigenous, afro-descendants and mestizos. The latter are tri-hybrid due to the influence of Native-American, European and African groups. In addition, they are mostly descendants of Spaniards and Indians and make up 60 percent of the population.